2007
DOI: 10.2223/jped.1671
|View full text |Cite
|
Sign up to set email alerts
|

Penile anthropometry in Brazilian children and adolescents

Abstract: Objetivo: Classicamente, o pênis tem duas funções: permitir a fertilização interna e direcionar o jato miccional. Entretanto, alterações objetivas do tamanho peniano podem levar ao diagnóstico de doenças. Além disso, é motivo comum de consulta médica a busca por parâmetros de normalidade do tamanho do pênis. Contudo, a antropometria do pênis da criança e do adolescente brasileiros ainda não foi devidamente estudada. O objetivo do estudo é realizar a antropometria do pênis de crianças e adolescentes brasileiros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
16
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 12 publications
1
16
0
1
Order By: Relevance
“…It has been reported that there is no significant increase in PL from age 0 to 5 years, with a slow rate of growth observed from 5 to 10 years and an increased rate from 11 to 18 years. 6 This finding has been corroborated by others. 7,8 Reference tables for PL are necessary to demonstrate a possible deviation from normal growth since a short penis may be the only sign of endocrinological pathology.…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…It has been reported that there is no significant increase in PL from age 0 to 5 years, with a slow rate of growth observed from 5 to 10 years and an increased rate from 11 to 18 years. 6 This finding has been corroborated by others. 7,8 Reference tables for PL are necessary to demonstrate a possible deviation from normal growth since a short penis may be the only sign of endocrinological pathology.…”
Section: Discussionsupporting
confidence: 71%
“…However, this study did not consider GDS or puberty. 6 Similarly Marshall and Tanner reported PLs of 12.5 to 14.5 cm at 12.5 years and 12.5 to 16.5 cm at 14.5 years. 3 In another study Schonfeld and Beebe reported mean Ϯ SD PL of 9.8 Ϯ 4.9 cm at 14 years.…”
Section: Discussionmentioning
confidence: 89%
“…Reassurance in these men has been demonstrated to be effective, with 86% of a recent population presenting with concerns over penis size successfully reassured when given evidence of comparison with their peer group [14]. A question is whether men with SPA should be compared with a reference range including those men with micropenis, as in the pediatric study of Gabrich and colleagues [15]. Our feeling is that reassuring men that they are "larger" than a micropenis would be cold comfort to them and the use of a nomogram looking at "normal" men is more likely to be of clinical use, but this is open to research.…”
Section: Discussionmentioning
confidence: 99%
“…In 2006, evaluation of 2126 children in Taiwan revealed normal penile length values of that country (5). Another study from Brazil (2) showed that 2010 children’s and adolescents’ penile length was measured and normal values of that country were established. In the latter study, there was no significant difference on 1‐ to 4‐year‐old children’s penile length with our age‐matched groups.…”
Section: Discussionmentioning
confidence: 99%